SEMIOTIC ANALYSIS IN INSTAGRAM LOGO - Eva Eriva Tandi Payuk; Zakrimal Zakrimal (JELLT (Journal of English Language and Language Teaching), 2020)
This article investigated about semiotic found in Instagram logo. This article used Instagram, because many people nowadays used Instagram to express themselves. Â The aim of this study is to find out the connotative and denotative meaning through Instagram. The writers used John theory to reveal this study. In this research, the writers applies the qualitative descriptive method. The method of collecting data is observation. The steps are choosing the logo that would be analyzed. The results indicate there are twelve data that have meaning from different logos on Instagram. They all have different functions based on the logo. The conclusion is Instagram as a social media application that allows users to share photos and videos, add captions, edit filters, engage with others, and explore the world by using this application.